High-Yield Synthesis of N4-(3-Chloro-4-fluorophenyl)-7-((4-methoxybenzyl)thio)quinazoline-4,6-diamine via N-(3-Chloro-4-fluorophenyl)-7-((4-methoxybenzyl)thio)-6-nitroquinazolin-4-amine - Susila Thapa; Jeanne L. Bolliger (Molbank)
The target compound, N4-(3-chloro-4-fluorophenyl)-7-((4-methoxybenzyl)thio)quinazoline-4,6-diamine, was synthesized in two steps from N-(3-chloro-4-fluorophenyl)-7-fluoro-6-nitroquinazolin-4-amine by a nucleophilic aromatic substitution, yielding N-(3-chloro-4-fluorophenyl)-7-((4-methoxybenzyl)thio)-6-nitroquinazolin-4-amine which was characterized by 1H NMR, 13C NMR, 19F NMR, and HRMS. Subsequent reduction yielded the target molecule, N4-(3-chloro-4-fluorophenyl)-7-((4-methoxybenzyl)thio)quinazoline-4,6-diamine. The structure of the target compound was confirmed by 1H NMR, 13C NMR, 19F NMR, HSQC, HMBC, HRMS, and FTIR.